Event related desynchronization and synchronization reveals different dysfunction in SCA with respect to EPM1 patients. Issue 1 (January 2019) - Visani, E.; Nanetti, L.; Mongelli, A.; Panzica, F.; Rossi Sebastiano, D.; Castaldo, A.; Franceschetti, S.; Mariotti, C.; Canafoglia, L.
Abstract : We evaluated patients with spinocerebellar ataxia (SCA) and Unverricht-Lundborg disease (EPM1) to compare motor related EEG modulation associated with selective cerebellar dysfunction or action myoclonus. We analyzed high-resolution EEG desynchronization/synchronization (ERD/ERS) in alpha and beta bands, occurring in response to a 'Go'and 'no-Go' motor tasks in 11 SCA, in 11 EPM1 patients and in 10 healthy controls. In 'Go' condition, alpha-ERD showed a similar time course in patients and controls, while in 'no-Go' condition SCA and EPM1 patients showed a significantly protracted ERD duration, compared to controls. The latency to reach maximal alpha ERD peak was significantly shortened in 'no-Go' with respect to 'GO' condition in controls and SCA patients, but not in EPM1. Only in SCA patients, the area under the ERD was similar on both hemispheres. In the beta band, ERS maximal amplitude was lower and the time to reach its maximal value was reduced only in EPM1 patients. Only in SCA patients the area under ERD was similar on both hemispheres. Both SCA and EPM1 patients showed a disordered ERD/ERS pattern, suggesting a defective ability of EPM1 in no-Go and post movement pattern, and a mainly defective lateralization in SCA patients.